Drug utilization study in ischaemic heart disease in a tertiary care hospital, Mangalore, India - Zachariah, Tittu George; K., Subramanyam; M., Pooja; Kempaller, Vinayak J. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The study of drug utilization is a component of a medical audit and periodic evaluation need to be done to enable suitable modifications in prescription of drugs to increase the therapeutic benefit and decrease the adverse effects. When new drugs are used additional information on safety and efficacy may be generated. Ischaemic heart disease (IHD) is a condition in which there is an inadequate supply of blood and oxygen to a portion of the myocardium. Medications for IHD include anti-platelet therapy, nitrates, statins, ACE inhibitors, beta blockers, CCB’s, diuretics. Methods: The study was carried out at cardiology department of K. S. Hegde Charitable Hospital for a period of one year from January 2015, and relevant retrospective data were also collected from hospital records for period pertaining to one year from 1/1/2013. Results: We assessed discharge summaries of 950 patients and found that majority of patients were males than females. The highest number of patients were in the age group of 51-60 years. Polypharmacy has been observed in our study. The average number of days spent by the patients in the hospital was 3.5 days. None of the drugs were prescribed using generic names, all the drugs (100%) were prescribed in brand names only. Common co-morbidities associated with IHD were hypertension and diabetes. Most commonly prescribed drugs for IHD were Aspirin, followed by Atorvastatin, Clopidogrel, and Nitrates. Conclusions: In our study, on analysing the drug prescription data it was observed that there was no statistically significant change in drug utilization between the two years.